Long-Term Effect of Salt Substitute on All-Cause and Cardiovascular Disease Mortality: An Exploratory Follow-Up of a Randomized Controlled Trial - Sun, Hao; Ma, Bing; Wu, Xiaomei; Wang, Hailong; Zhou, Bo (Frontiers in Cardiovascular Medicine, 2021)
Background: Salt substitute, a strategy for salt reduction, has been shown to decrease blood pressure and the incidence of hypertension. However, whether its hypotensive effect will reduce long-term mortality remains unclear. Our study reported an exploratory follow-up of mortality outcomes from previous randomized controlled trial to assess the long-term effect of low-sodium salt on total and cardiovascular disease (CVD) mortality. Methods: Participants who completed a previous 3-year double-blind randomized controlled trial were followed up from 2009 to 2019 to collect mortality data. Multivariable Cox regression models were used to evaluate the association between low-sodium salt intervention and all-cause and CVD mortality. Results: Four hundred and forty participants completed the intervention trial, of which 428 participants had death outcome data recorded after 10 years follow-up: 209 in a salt substitute group and 219 in a normal salt group. Fifty participants died during follow-up, 25 died due to CVD. No significant differences in relative risks were found for all-cause mortality (HR=0.81, 95% confidence interval (CI): 0.46-1.42) and CVD mortality (HR=0.58, 95% CI: 0.26-1.32) in unadjusted analyses. After adjusted with age and alcohol drinking status, there were significant reductions for stroke mortality among all participants (HR=0.26, 95% CI: 0.08-0.84) and for CVD mortality (HR=0.38, 95% CI: 0.16-0.92) and stroke mortality (HR=0.25, 95%CI: 0.08-0.82) among hypertensive participants. Conclusions: Compared to normal salt, salt substitute might reduce the risk of CVD death, especially stroke mortality among hypertensive patients. Our exploratory follow-up results provide potential evidence that low-sodium salt may be an accessible and effective strategy for prevention of CVD events, but definitive randomized controlled trials are warranted.